Novel Peptide for Attenuation of Hyperoxia-induced Disruption of Lung Endothelial Barrier and Pulmonary Edema via Modulating Peroxynitrite Formation - Kondrikov, Dmitry (J Biol Chem, 2014)
Pulmonary damages of oxygen toxicity include vascular leakage and pulmonary edema. We have previously reported that hyperoxia increases the formation of NO and peroxynitrite in lung endothelial cells via increased interaction of endothelial nitric oxide (eNOS) with β-actin. A peptide (P326TAT) with amino acid sequence corresponding to the actin binding region of eNOS residues 326–333 has been shown to reduce the hyperoxia-induced formation of NO and peroxynitrite in lung endothelial cells. In the present study, we found that exposure of pulmonary artery endothelial cells to hyperoxia (95% oxygen and 5% CO(2)) for 48 h resulted in disruption of monolayer barrier integrity in two phases, and apoptosis occurred in the second phase. NOS inhibitor N(G)-nitro-l-arginine methyl ester attenuated the endothelial barrier disruption in both phases. Peroxynitrite scavenger uric acid did not affect the first phase but ameliorated the second phase of endothelial barrier disruption and apoptosis. P326TAT inhibited hyperoxia-induced disruption of monolayer barrier integrity in two phases and apoptosis in the second phase. More importantly, injection of P326TAT attenuated vascular leakage, pulmonary edema, and endothelial apoptosis in the lungs of mice exposed to hyperoxia. P326TAT also significantly reduced the increase in eNOS-β-actin association and protein tyrosine nitration. Together, these results indicate that peptide P326TAT ameliorates barrier dysfunction of hyperoxic lung endothelial monolayer and attenuates eNOS-β-actin association, peroxynitrite formation, endothelial apoptosis, and pulmonary edema in lungs of hyperoxic mice. P326TAT can be a novel therapeutic agent to treat or prevent acute lung injury in oxygen toxicity.